2019
DOI: 10.3892/ol.2019.9941
|View full text |Cite
|
Sign up to set email alerts
|

Role of miRNA‑21 in the diagnosis and prediction of treatment efficacy of primary central nervous system lymphoma

Abstract: Primary central nervous system lymphoma (PCNSL) has a poor prognosis and requires early diagnosis and treatment. The aim of the present study was to investigate the difference between microRNA-21 (miRNA-21) expression in the plasma and cerebrospinal fluid (CSF) of patients with PCNSL, and to discuss the importance of miRNA-21 in its diagnostic and therapeutic evaluation. The research subjects were confirmed as patients with PCNSL with histopathological lesions at The First Affiliated Hospital of Harbin Medical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 34 publications
2
29
0
Order By: Relevance
“…At present, CSF examination is a routine clinical procedure for most PT-DLBCL patients. This approach is able to measure biomolecules such as glucose, protein, and miRNAs in CSF, which may help to improve the accuracy of CNS involvement diagnosis and prognostic estimation 8…”
Section: Introductionmentioning
confidence: 99%
“…At present, CSF examination is a routine clinical procedure for most PT-DLBCL patients. This approach is able to measure biomolecules such as glucose, protein, and miRNAs in CSF, which may help to improve the accuracy of CNS involvement diagnosis and prognostic estimation 8…”
Section: Introductionmentioning
confidence: 99%
“…MiRNA expression of PCNSL has been studied using different methods such as RT-PCR [28-38], microarray [36, 39], in situ hybridization [37, 38], next-generation sequencing (NGS) [35] and NanoString [38] technologies on various tissue types including brain biopsy specimens (FFPE [32, 37, 39] or fresh [36]), cerebrospinal fluid (CSF) [28-31, 33, 38] and peripheral blood [35], serum [34] or plasma [33]. It has been shown and further confirmed that the combined detection of miR-21, miR-19b and miR-92a in CSF allowed a reliable diagnosis of PCNSL.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, these miRNAs emerge as promising tools in treatment monitoring and follow-up [28, 29], similarly to U2 small nuclear RNA fragments [30]. In addition, plasma miR-21 may serve as a diagnostic [33], and serum miR-21 both as a diagnostic and prognostic marker for PCNSL [34]. Other miRNAs with prognostic value in PCNSL include miR-151a-5p and miR-151b, together with 10 additional miRs [35].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, discovery of molecular biomarkers from the cerebrospinal fluid (CSF) 4 and the serum 5 have become an area of extensive research. Among the novel biomarkers, microRNAs (miRNAs) have been considered in PCNSL diagnosis because the primary central nervous system diffuse large B-cell lymphoma (PCNS-DLBCL) has a distinct miRNA signature compared to that in the germinal center (GC)-DLBCL and the non-GC-DLBCL 6 . Despite this finding, there is a limited clinical application of miRNA.…”
Section: Introductionmentioning
confidence: 99%